Partnerstwo przejawem przedsiębiorczości - Bembenek, Bogusław (Partnership as a Result of Enterprise, 2006)
In the paper there was presented an enterprising character of partnership. The author understands under partnership some dynamic process that takes place in time, that is created and formed by interactions of partners. The author shows, that the partnership is some effective response for opportunities and threaths which come from the turbulent surroundings and it makes possible to boost enterprise competitiveness on the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 227-235